2014
DOI: 10.1063/1.4904412
|View full text |Cite
|
Sign up to set email alerts
|

Low power ovonic threshold switching characteristics of thin GeTe6 films using conductive atomic force microscopy

Abstract: Minimizing the dimensions of the electrode could directly impact the energy-efficient threshold switching and programming characteristics of phase change memory devices. A ∼12–15 nm AFM probe-tip was employed as one of the electrodes for a systematic study of threshold switching of as-deposited amorphous GeTe6 thin films. This configuration enables low power threshold switching with an extremely low steady state current in the on state of 6–8 nA. Analysis of over 48 different probe locations on the sample reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…3(a)) show that compliance currents smaller than 100 µA have no trivial effect on the switching characteristics, at least for a short number of cycles (100 cycles). Recent studies on GeTe 6 29, 43 also showed OTS behaviour with a threshold voltage of 1.6 to 2.4 V, depending on the measurement type (AC or C-AFM) or thickness of the films (20 or 190 nm) and a holding voltage of 0.7 V. The results are comparable to our findings.
Figure 2GeTe 6 switching characteristics for a 135 nm device. ( a ): Average of 100 DC alternate polarity cycles.
…”
Section: Resultssupporting
confidence: 89%
“…3(a)) show that compliance currents smaller than 100 µA have no trivial effect on the switching characteristics, at least for a short number of cycles (100 cycles). Recent studies on GeTe 6 29, 43 also showed OTS behaviour with a threshold voltage of 1.6 to 2.4 V, depending on the measurement type (AC or C-AFM) or thickness of the films (20 or 190 nm) and a holding voltage of 0.7 V. The results are comparable to our findings.
Figure 2GeTe 6 switching characteristics for a 135 nm device. ( a ): Average of 100 DC alternate polarity cycles.
…”
Section: Resultssupporting
confidence: 89%
“…17 However, a ReRAM cross-point array still requires much lower leakage current for high-density memory applications. Furthermore, the ovonic threshold switch has a very complicated composition of AsTeGeSiN with a narrow process margin.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical characteristics of GeSe ovonic threshold switches were shown to be highly tunable with doping material and concentration, which makes them versatile for GST phase-change memory applications [26][27][28][29][30]. In addition, GeTe 6 was shown to have excellent electrical properties, but may not meet the thermal stability needed [31][32][33][34][35]. This is also subject to the memristor and selector device dimensions which is expected to be very small for commercialised technologies.…”
Section: Discussion and Summarymentioning
confidence: 99%